2015
DOI: 10.1021/jf506192s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Different Botanical Origin Honeys Produced by Sicilian Black Honeybees (Apis mellifera ssp. sicula)

Abstract: In 2008 a Slow Food Presidium was launched in Sicily (Italy) for an early warning of the risk of extinction of the Sicilian native breed of black honeybee (Apis mellifera L. ssp sicula). Today, the honey produced by these honeybees is the only Sicilian honey produced entirely by the black honeybees. In view of few available data regarding the chemical composition of A. mellifera ssp. sicula honeys, in the present investigation the chemical compositions of sulla honey (Hedysarum coronarium L.) and dill honey (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
5
27
0
Order By: Relevance
“…In other terms, the reducing capacity of radical scavengers measured through the DPPH and ABTS •+ cannot be simply translated to their activity against • Mb[Fe IV =O], since interaction with the transient radical site of the protein, or access to the heme hydrophobic pocket demands suitable size, three-dimensional structure and physicochemical feature of the compound (Jongberg et al, 2014). As reported (Mannina et al, 2015; Tenore et al, 2012), phenolic acids represent approximately 83% of TPC, whereas quercetin and kaempferol are the most representative flavonoids in lemon, orange, medlar, almond, sulla and dill honey produced by Apis mellifera ssp. sicula .…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…In other terms, the reducing capacity of radical scavengers measured through the DPPH and ABTS •+ cannot be simply translated to their activity against • Mb[Fe IV =O], since interaction with the transient radical site of the protein, or access to the heme hydrophobic pocket demands suitable size, three-dimensional structure and physicochemical feature of the compound (Jongberg et al, 2014). As reported (Mannina et al, 2015; Tenore et al, 2012), phenolic acids represent approximately 83% of TPC, whereas quercetin and kaempferol are the most representative flavonoids in lemon, orange, medlar, almond, sulla and dill honey produced by Apis mellifera ssp. sicula .…”
Section: Resultssupporting
confidence: 58%
“…sicula . Interestingly, the highest amount of rutin, a flavonol shown to be effective in reducing the perferryl form of heme-proteins (Grinberg et al, 1994), has been reported in sulla (Mannina et al, 2015) and medlar (Tenore et al, 2012) honeys, that indeed were highly effective in deactivating the perferryl-Mb radical species, despite a low or modest TPC (Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in almost all cases, unambiguous NMR assignments can only be derived by 2D analysis, because molecular conformation, chemical shifts, and vicinal J couplings are affected by the food matrix. Details about the spectral assignment and the determination of various classes of compounds in foods using standard NMR methods have been previously discussed and can be found in previous publications (Cheng & Neiss, ; Christophoridou & Dais, ; Dais & Hatzakis, ; Fotakis et al., ; Kazalaki et al., ; Mannina et al., ; Marcone et al., ; Nilsson et al., ; Nord, Vaag, & Duus, ; Petersen et al., ; Siddiqui et al., ; Spyros & Dais, ; Zhao et al., ). Table shows key applications of NMR spectroscopy in food compositional analysis and structure elucidation.…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%
“…The steady development and updating of a palynological database could be very important for the study of biodiversity, because it would provide an additional tool to identify, for example, cases of introduction of non-native species, cases of speciation or hybridization. This study was also necessary for another more complex work, which consists of melissopalynological analysis of the honeys both through the use of optical microscopy, for the recognition of pollen present in honey through comparison with the data present in our database, and through the use of Molecular Biology techniques, such as DNA extraction, PCR and real-time PCR, which will allow a more precise analysis (Loveaux et al, 1978;Simonetti et al, 1989;Persano Oddo et al, 1995;Schievano et al, 2013;Mannina et al, 2015).…”
Section: Results and Conclusionmentioning
confidence: 99%